What is the impact of surface modifications and particle size on commercial titanium dioxide particle samples? – A review of in vivo pulmonary and oral toxicity studies – Revised 11-6-2018. (1st March 2019) - Warheit, David B.; Brown, Scott C.
Abstract: There is an ongoing discussion on the influence of surface-modifications on the toxicity of commercial particulate materials and how alterations in physical-chemical properties of surfaces impact toxicity. Titanium dioxide (TiO2 ) is a poorly soluble particulate material of significant socioeconomic importance that largely exists as surface-modified particle-types in commerce. The observed toxicological effects of TiO2 are primarily due to particle effects rather than substance chemistry, as such TiO2 is commonly considered to be a poorly soluble low toxicity (PSLT) particle. This review provides an overview of the effect of surface modifications on the pulmonary and oral toxicity of commercial TiO2 particles with emphasis on in vivo studies with appropriate controls, and where both surface modified and untreated materials are present in the same study. Published literature findings involving pulmonary and oral exposures to surface modified TiO2 particles were reviewed and evaluated for quality and commercial relevance. Suitable publications involving animal studies were identified and summarized. Several studies were identified that have evaluated commercially-relevant surface-modified forms of titanium dioxide with appropriate data quality and with direct comparison to untreated counterparts. Hydrophilic inorganic surface modifications including silica, alumina/alumina hydroxide depositions have been tested along with common hydrophilic and hydrophobic-organic surface treatments. The results for both pigmentary and nanoscale materials demonstrate similar behaviour and indicate limited impact of particle size, surface chemistry, surface charge and surface wettability on observed pulmonary or oral toxicity effects. The low intrinsic toxicity of the TiO2 base particle and evaluated surface modifications may account for the observed outcomes. A few published studies have drawn different conclusions; however, these were either not conducted using commercial TiO2 samples (with surface coatings), had several confounding variables to investigate, or were carried out using mouse strains. The differences in experimental designs are described. The identified pulmonary and oral toxicity studies largely indicate that surface modifications and particle size alone have little or no impact on the lung toxicity of TiO2 particles, following pulmonary exposures when all constituent materials are comprised of chemicals of low specific toxicity particles. In addition, based upon the results of 2 oral toxicity studies, one with surface treated TiO2 particles (OECD 408) and one without surface treated (OECD 407) TiO2 particles, there appears to have been no adverse impact on toxicity with the surface-coated material, as both studies produced no adverse effects at the very high doses tested.